Stakeholder roles approach for sustainability assessment in the context of heritage tourism development the case of Angeles City, Pampanga - Vergara, Norma Jean A.; David Leonides T. Yap (Quezon City School of Urban and Regional Planning, University of the Philippines Diliman, 2017)
This study aimed to make an assessment on the perceived sustainability of Angeles City's heritage tourism development using stakeholder analysis. It identified the stakeholder roles and prevailing relationships among stakeholder groups and used this analysis in assessing the current state of economic, environmental and socio-cultural sustainability of the local heritage tourism industry. It employed a qualitative research methodology, in which the primary data gathered comprised of in-depth interviews with key informants belonging to the public sector, private sector, non-government organizations (NGOs) and local community sector, as well as non-participant observation in the study site. Content analysis was the main analytical used in processing and interpreting data. The study found that stakeholders view the public sector as the group that drives the overall direction of heritage tourism development of Angeles City. The private sector contribution, it was found, was limited to their expected cooperative role relating to government-imposed policies and regulations on the design and structure of business establishments inside the heritage zone. The NGO sector was found to play the important role of being in the forefront of advancing heritage preservation efforts, while the local community sector role was centered on being the supporters and sustainers of heritage tourism development. On existing stakeholders dynamic, the study found the public sector to be dominant player among stakeholder relationships as they hold the mandate for heritage tourism development and control much of the resources that advance this advocacy. Generally speaking, the presence of cooperation networks comprising various stakeholders is sound in that the players are able to work on their organizational and outlook similarities so they are able to generally maintain amicable social relations, interactions and flows of communication. In the sustainability assessment based on the stakeholder analysis, it was found that Angeles City is currently managing a heritage tourism based on stakeholder analysis, it was found that Angeles City is currently managing a heritage tourism industry that is perceived to be economically and environmentally unsustainable, but socio-culturally sustainable. At the moment, the tourism trade inside the heritage zone not significant enough to positively impact the local economy, and the same area is threatened by rapid land use conversion in favor of commercial establishments. Despite these undesirable impacts, the city appears to maintain the socio-cultural sustainability of its heritage tourism development as its stakeholders participate in active built and intangible cultural tourism product development, cultivate a deeper sense of pride in belonging to their place and a growing sentiment to strengthen the heritage tourism brand of the city. The study posits that given the perceived sustainable socio-cultural character of Angeles City's heritage tourism development, overall sustainability is still attainable as economic and environmental interventions are easier to employ to effect immediate impacts than would be the case if an area is dealing with poor socio-cultural sustainability.
Thesis (Master of Arts in Urban and Regional Planning)--University of the Philippines Diliman, 2017.
Keywords: Heritage tourism -- Philippines -- Angeles City Pampanga); Tourism -- Philippines -- Angeles City (Pampanga); Sustainabilty -- Philippines -- Angeles City (Pampanga)